An experimental test of state–behaviour feedbacks: gizzard mass and foraging behaviour in red knots. (2nd March 2017) - Mathot, Kimberley J.; Dekinga, Anne; Piersma, Theunis
Summary: Animals frequently exhibit consistent among‐individual differences in behavioural and physiological traits that are inherently flexible. Why should individuals differ consistently in their expression of labile traits? Recently, positive feedbacks between state and behaviour have been proposed as a possible explanation for the maintenance of consistent among‐individual differences in both state and behaviour. If state affects behaviour, and behaviour reciprocally affects state, then differences in either state or behaviour that arise among individuals even by chance could be maintained over extended periods of time. We tested for positive feedbacks experimentally using wild‐caught red knots ( Calidris canutus islandica ). In the wild, knots exhibit consistent among‐individual differences in digestive physiology (the mass of the muscular part of the stomach, the gizzard) and foraging behaviour (diet), two inherently labile traits. Experimentally manipulated diet quality had a large effect on gizzard mass. Experimentally manipulated gizzard mass reciprocally influenced total food eaten during ad libitum trials. The effect of gizzard mass on diet choice, though in the predicted direction, was not statistically significant. Individuals exhibited consistent differences in foraging behaviour of unknown origin independent of current gizzard mass, as well as large residual unexplained variance in foraging behaviour. These two sources of variation in foraging behaviour overruled the gizzard mass‐dependent foraging behaviour and hence eroded the treatment‐related differences in gizzard mass. We conclude that positive feedbacks between diet choice and gizzard mass play at best a limited role in maintaining among‐individual variation in gizzard mass in red knots. Furthermore, we suggest that many models of state–behaviour feedbacks likely overestimate their potential importance in maintaining long‐term among‐individual variation in labile traits because most models of state–behaviour feedbacks fail to account for the effects of additional factors that may act to disrupt the feedback loops. The among‐individual differences in diet choice observed during solitary foraging trials eroded the consistent among‐individual differences in gizzard mass observed following periods of staple diet treatments in which knots foraged in social groups. Social foraging interactions may play an important role determining the expression of foraging behaviours such as intake rate that in turn influence gizzard mass. Further studies are needed to experimentally test the role of social interactions as a mechanism generating consistent among‐individual differences in foraging behaviours and gizzard mass. A lay summary is available for this article. Abstract : Lay Summary